Elucidation of the anti-inflammatory compound present in Jatropha curcas Linn Root and its mode of action - Othman, Ahmad Razi (2016)
Jatropha curcas Linn. (family Euphorbiaceae) is a drought resistant shrub which is widely grown in Central and South America, South-east Asia, India and Africa. The plant has been considered a traditional herb in many parts of the world. In inflammatory treatment, it has been widely accepted that non-steroidal anti-inflammatory drugs (NSAIDs) can effectively prevent inflammation. However, several studies have also revealed side effects resulting from prolonged use of NSAIDs, which include the possibility of several chronic diseases such as gastrointestinal ulcers, adverse cardiovascular side-effects, and Alzheimer’s disease. Hence, alternative medicine based on natural herbs should be considered in inflammation treatment. Furthermore, the use of herbal remedies is gaining acceptance in various pharmaceutical applications. Although several studies have shown different parts of J. curcas possessed anti- inflammatory activity, but the nature of the compounds involved and the mode of action are not well understood. Hence, before the herbal products can be made available, detail information regarding the nature of bioactive compounds and the mode of action have to be understood. Thus, the main objective of this study was to elucidate the anti- inflammatory compounds from J. curcas plant and to determine the mode of action. The experiments conducted include screening of different parts of plant extracts for the anti- inflammatory activity by using Murine monocytic macrophage RAW 264.7 cells line, purifying and elucidating the structure of the anti-inflammatory compounds, determining the mode of action of the purified compounds on the inflammation pathway and the inflammatory enzymes affected. Anti-inflammatory activity was assayed by determining the inhibition of nitric oxide production in the RAW 264.7 cells, while cytotoxicity activity was determined by the (3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) MTT assay. In the initial study, it was observed that Jatropha root methanolic extract showed anti-inflammatory property higher than other plant parts (leaves, fruits and stem bark), but with high cytotoxicity towards Murine monocytic macrophage RAW 264.7 cells line. Subsequently, the root extract was fractionated into fractions with different solvents (hexane, chloroform and ethyl acetate). The hexane fraction possessed high anti-inflammatory property, but with high cytotoxicity towards cell growth. Analysis of the compounds present in the hexane fraction by gas chromatography mass spectrometry (GC-MS) showed the presence of many compounds belonging to the terpene group which probably caused the cytotoxicity. Further purification was conducted by using an open column system to isolate and purify the compounds with anti-inflammatory activity without cytotoxicity. Five spots (labeled H-1, H-2,3, H-4 and H-5) from the hexane fraction were obtained. The anti-inflammatory assay showed the compounds present in spot H-4 and H-5 possessed high anti-inflammatory without cytotoxicity activity. Analysis of compounds present in these two spots by GC-MS showed the presence of hexadecanoic and octadecanoic acid groups in both spots. The high performance liquid chromatography (HPLC) analysis of spot H-4 showed two peaks (A and B), with eluent A (peak A) displaying better anti-inflammatory activity than eluent B (peak B), without being toxic to the cell growth. Identification of the compound present in eluent A by liquid chromatography-tandem mass spectrometry (LC-MS/MS) indicated that the compound belonged to the octadecanoic acid group. Further analysis conducted by using NuclearMagnetic Resonance (NMR) showed that this active compound was a long chain of hydrocarbons with a carboxylic group attached at the end, thus confirming that the active compound belonged to octadecanoic acid group. To determine the mode of action in the anti-inflammatory activity, the fluorescence staining assay was conducted to observe the translocation of the NF-ĸB subunit (involved in inflammatory signaling pathway) from the cytoplasm into the nuclei of the RAW 264.7 cells. The results showed that octadecanoic acid did not inhibit the translocation of p65 subunit, thus could not inhibit expression of inflammatory genes. Similarly, in the gene expression study by qualitative Reverse Transcriptase PCR, genes for phospholipase A2 (PLA2), cyclooxygenase-1 (COX-1), cyclooxygenase-2 (COX-2), 5-lipoxygenase (5-LOX) and inducible nitric oxide synthase (iNOS) involved in inflammatory signaling pathway were not affected by octadecanoic acid added to the cells at various concentrations (0.125 mg/mL – 1.0 mg/mL). In the inflammatory enzyme assays, only PLA2 activity, but not COX-1, COX-2, and 5-LOX were inhibited. An IC50 analysis showed that at concentrations of 0.24 mg/mL, octadecanoic acid inhibited 50% of PLA2 activity. As a conclusion, the present study showed that J.curcas plant possessed anti-inflammatory activity, especially the roots and several compounds belonging to the terpene group present in the root, might contributed to the cytotoxicity of the root extract. The anti-inflammatory compound was identified to be octadecanoic acid and was found to inhibit PLA2 enzyme activity (as the possible mode of action) by competing with the enzyme substrate as indicated by the IC50 analysis, where PLA2 activity was only inhibited at high concentrations of octadecanoic acid.